2014
DOI: 10.1024/0300-9831/a000214
|View full text |Cite
|
Sign up to set email alerts
|

Higher Bioavailability of Organic Bound Zinc from High Zinc-Enriched Fungi

Abstract: The organic forms of trace elements are considered more bioavailable than the inorganic forms. Although yeast can enrich metal elements and convert inorganic zinc to organic species, its tolerability and transforming capacity are limited. It would therefore be very interesting to look for higher conversion and accumulation in zinc fungi to obtain organic bound zinc from the natural environment. In this paper, potato dextrose agar (PDA) medium containing 800 μg/mL zinc was used for initial screening, with twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In our previous studies, we have shown that Fusarium oxysporum has greater accumulation of zinc, with a higher bioavailability than the supplement zinc gluconate (Zhang et al, 2014). Following on from this, we have conducted extensive screening and discovered a new strain belonging to the genus Candida, which also possess the zinc enriching activity and in this paper, we describe this novel yeast species and examine its ability to enrich zinc.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…In our previous studies, we have shown that Fusarium oxysporum has greater accumulation of zinc, with a higher bioavailability than the supplement zinc gluconate (Zhang et al, 2014). Following on from this, we have conducted extensive screening and discovered a new strain belonging to the genus Candida, which also possess the zinc enriching activity and in this paper, we describe this novel yeast species and examine its ability to enrich zinc.…”
Section: Introductionmentioning
confidence: 91%
“…The following thermal cycling program was used; 32 cycles of 3 min at 94 °C, 30 s at 94 °C, 30 s at 56 °C, 50 s at 72 °C, followed by 7 min at 72 °C. The amplified PCR products were separated by 1% agarose gel electrophoresis and sent to Shanghai Biotech Bioengineering Technology Services for sequencing (Zhang et al, 2014). After obtaining the sequence, a BLAST search was performed and 10 strain sequences with similar homology were found (Altschul et al, 1990).…”
Section: Phenotypic Characteristics and Molecular Identificationmentioning
confidence: 99%
See 3 more Smart Citations